Budget impact analysis of drugs for ultra-orphan non-oncological diseases in Europe. (February 2014) - Schlander, Michael; Adarkwah, Charles Christian; Gandjour, Afschin
<x xml:space="preserve">Abstract</x> Background/aim: Ultra-orphan diseases (UODs) have been defined by a prevalence of less than 1 per 50, 000 persons. However, little is known about budget impact of ultra-orphan drugs. Methods: For analysis, the budget impact analysis (BIA) had a time horizon of 10 years (2012–2021) and a pan-European payer's perspective, based on prevalence data for UODs for which patented drugs are available and/or for which drugs are in clinical development. Results: A total of 18 drugs under patent protection or orphan drug designation for non-oncological UODs were identified. Furthermore, 29 ultra-orphan drugs for non-oncological diseases under development that have the potential of reaching the market by 2021 were found. Total budget impact over 10 years was estimated to be €15, 660 and €4965 million for approved and pipeline ultra-orphan drugs, respectively (total: €20, 625 million). Conclusion: The analysis does not support concerns regarding an uncontrolled growth in expenditures for drugs for UODs.